2020
DOI: 10.1002/jemt.23516
|View full text |Cite
|
Sign up to set email alerts
|

Macro‐ and microscopic study on the tongue and lingual papillae of Bison bonasus hybrid as an interspecific species (Bos taurus × Bison bonasus)

Abstract: Nowadays the processes of crossing of different mammalian species are well characterized in light of genetics, and possibility of reproduction. Generally, lack detailed studies on changes in anatomy and histology of internal systems of hybrids. Bison bonasus hybrid is an interspecific species between the bull of European bison (Bison bonasus), and female of domesticated cattle (Bos taurus). To study the anatomy of tongue and distribution of lingual papillae on Bison bonasus hybrid tongue, a stereomicroscopic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Also, most herbivorous mammalian species have this distinct lingual prominence (Abumandour & El‐Bakary, 2013; Kandyel et al, 2021; Massoud & Abumandour, 2019). Our findings revealed that the presence of the median lingual sulcus on the dorsal surface of the apex, similar most ruminant species regardless of their feeding strategies (Ding et al, 2016; El‐Bakary & Abumandour, 2017; Erdoğan & Sağsöz, 2018; Jackowiak et al, 2017; Mahdy et al, 2021) while it was observed on the dorsal surface of the Bison bonasus hybrid tongue (Plewa & Jackowiak, 2020), but it extended from the apex to the body in fallow deer (Jackowiak et al, 2017). Also, the median sulcus was observed in other non‐ruminant herbivorous animals (Abumandour & El‐Bakary, 2013; Massoud & Abumandour, 2019).…”
Section: Discussionsupporting
confidence: 50%
“…Also, most herbivorous mammalian species have this distinct lingual prominence (Abumandour & El‐Bakary, 2013; Kandyel et al, 2021; Massoud & Abumandour, 2019). Our findings revealed that the presence of the median lingual sulcus on the dorsal surface of the apex, similar most ruminant species regardless of their feeding strategies (Ding et al, 2016; El‐Bakary & Abumandour, 2017; Erdoğan & Sağsöz, 2018; Jackowiak et al, 2017; Mahdy et al, 2021) while it was observed on the dorsal surface of the Bison bonasus hybrid tongue (Plewa & Jackowiak, 2020), but it extended from the apex to the body in fallow deer (Jackowiak et al, 2017). Also, the median sulcus was observed in other non‐ruminant herbivorous animals (Abumandour & El‐Bakary, 2013; Massoud & Abumandour, 2019).…”
Section: Discussionsupporting
confidence: 50%
“…Conical papillae were found on the lingual torus, which has often been described in various other ruminants (Adnyane et al, 2011;Emura et al, 2011a;2011b;Emura et al, 2013, Emura et al 2000, Erdogan & Pérez, 2013bFarrag et al, 2022;Harem et al, 2011;Jackowiak et al, 2017;Karadag Sa et al, 2010;Plewa & Jackowiak, 2020;Yoshimura et al, 2000;Zheng & Kobayashi, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…Conical papillae were found on the lingual torus, which has often been described in various other ruminants (Adnyane et al, 2011; Emura et al, 2011a; 2011b; Emura et al, 2013, Emura et al 2000, Erdogan & Pérez, 2013b; Farrag et al, 2022; Harem et al, 2011; Jackowiak et al, 2017; Karadag Sa et al, 2010; Plewa & Jackowiak, 2020; Yoshimura et al, 2000; Zheng & Kobayashi, 2006). Some of the conical papillae in the okapi could be described as lenticular papillae; this term is often used for reduced, very flattened papillae on the lingual torus in ruminants (Plewa & Jackowiak, 2020). In the giraffe, all mechanical papillae are classified as conical and lenticular (Emura et al, 2013, Pérez et al 2012), and conical papillae are not limited to the lingual torus, also being found on the apex and body.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation